(3GdJPcQI aj Yde GdcdGes ((3eOjfI WaGQ s)
(3ChdgG (B:s
(3gPg JPcQI JTJed Ydi HjGf CMcGe GdeYdheGJ aChUGagG hJLeY Edi GdEjLGR ai Gdbhd s
(3BNQgG (B:s
(3hdjS GdJhba ai Pdc eeG jVQ ai TF ef GdCUhd s
(3LYdg GdeUfa Ydi gjFI SDGd hLhGH jJaQY efg aUhds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs